Blood Cell Profiles of the Tadpoles of the Dubois's Tree Frog, Polypedates teraiensis Dubois, 1986 (Anura: Rhacophoridae) - Madhusmita Das; Pravati Kumari Mahapatra (The Scientific World Journal)
The present paper describes a sequential study of the leukocyte profiles and the changes in morphometry and morphology of erythrocytes in the tadpoles of Polypedates teraiensis during their development and metamorphosis, that is, transfer from an aquatic mode to a terrestrial mode of life. Blood smears of 21 different stages (Gosner stage 26 to 46) of tadpoles were investigated. Population of erythrocytes was heterogeneous in population represented by various forms (oval, elliptical or rounded cells, comma shaped, teardrop shaped, schistocytes, senile erythrocytes, crenulated RBCs). Correlation between various morphometric values of erythrocytes was determined with different developing stages of tadpoles. Amongst the leucocytes, the lymphocytes were the most abundant cells followed by neutrophils. Neutrophils and monocytes showed varied morphologic forms. The percentage of lymphocytes and neutrophils showed a negative whereas percentage of eosinophil, basophil, and monocytes showed a positive correlation with the developmental stages of tadpoles. Blood platelets were also observed, which were rounded in shape and found in aggregates.